2018
DOI: 10.1093/cercor/bhx338
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With the Neutralizing Antibody Against Repulsive Guidance Molecule-a Promotes Recovery From Impaired Manual Dexterity in a Primate Model of Spinal Cord Injury

Abstract: Axons in the mature mammalian central nervous system have only a limited capacity to grow/regenerate after injury, and spontaneous recovery of motor functions is therefore not greatly expected in spinal cord injury (SCI). To promote functional recovery after SCI, it is critical that corticospinal tract (CST) fibers reconnect properly with target spinal neurons through enhanced axonal growth/regeneration. Here, we applied antibody treatment against repulsive guidance molecule-a (RGMa) to a monkey model of SCI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 55 publications
3
36
0
Order By: Relevance
“…We used an anti-human RGMa antibody that was raised against the C-terminal sequence of human RGMa 21,35 . Neutralization of RGMa by delivery of C-terminal antibodies has been demonstrated to promote axonal growth in models of spinal cord trauma in rats 21,35 and monkeys 39 .…”
Section: Discussionmentioning
confidence: 99%
“…We used an anti-human RGMa antibody that was raised against the C-terminal sequence of human RGMa 21,35 . Neutralization of RGMa by delivery of C-terminal antibodies has been demonstrated to promote axonal growth in models of spinal cord trauma in rats 21,35 and monkeys 39 .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported to express in the glial scar and myelin and is accumulated in lesioned sites after a traumatic injury of the spinal cord and brains in rodents [10]. In addition to rodents, administration of neutralizing antibody against RGMA was found to lead to recovery from impaired manual dexterity in a monkey model of SCI [12]. On this basis, we further modified RGMA expression in the SCI rat models.…”
Section: Discussionmentioning
confidence: 98%
“…RGMA is a GPI-linked glycoprotein that exists in soluble and membrane-bound forms and suppresses neurite growth by binding to neogenin, its neuronal receptor [10]. Correspondingly, inhibition of either RGMA or neogenin was found to promote neuronal survival and functional recovery after SCI [11,12]. The signal transducer and activator of transcription 3 (STAT3) signaling is implicated in multiple inflammatory responses by regulating some proinflammatory cytokines such as interleukin-6 (IL-6) and IL-17, and its downregulation was found to reduce spinal cord neuroinflammation and promote neuronal functional recovery after SCI [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, CT/MRI fusion has been validated for the postoperative assessment of electrodes in many studies [38][39][40]. In gamma knife radiosurgery, Nakagawa et al [41] showed more distortion with stereotactic MRI than with a 3-T image co-registered to a stereotactic CT. Thus, whatever preoperative imaging system is chosen, a postoperative MRI is the only way to validate the process.…”
Section: Co-registration Computed Tomography and Mrimentioning
confidence: 99%